Alcohol-resistant transparent high-toughness PMMA / SAN resin composition as well as preparation method and application thereof

By adding MBS toughening agent and polyetheramide block copolymer to the PMMA/SAN resin, the group distribution ratio is optimized, and the problem of PMMA/SAN resin is easily broken when exposed to alcohol is solved, achieving both the high transparency, good mechanical properties and alcohol resistance of the material.

CN119875279APending Publication Date: 2025-04-25KINGFA SCI & TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510043750.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing PMMA/SAN resins are prone to microcracks or breaks when exposed to alcohol, resulting in limited application in products that are frequently exposed to alcohol, and it is difficult to take into account transparency, mechanical properties and alcohol resistance.

Method used

PMMA and SAN are used as matrix resins to optimize the ratio of each component, and MBS toughener and polyetheramide block copolymer are added, which has good solvent resistance and fluidity, and can enrich on the surface and resist the erosion of organic solvents.

Benefits of technology

The excellent impact toughness, good light transmission properties and significantly enhanced alcohol resistance of the PMMA/SAN resin composition are achieved, and the damage to the material can be effectively prevented by alcohol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an alcohol-resistant transparent high-toughness PMMA / SAN resin composition as well as a preparation method and application thereof, and relates to the technical field of high polymer materials. The PMMA / SAN resin composition is prepared from the following components in parts by weight: 30 to 60 parts of PMMA resin, 10 to 30 parts of SAN resin, 15 to 30 parts of MBS (Methyl Methacrylate-Butadiene-Styrene) flexibilizer and 5 to 30 parts of polyether amide block copolymer, the content of acrylonitrile in the SAN resin is 18 to 25 weight percent. According to the PMMA / SAN resin composition disclosed by the invention, the PMMA resin and the SAN resin are adopted as matrix resin, the proportion of all the components is optimized, and the MBS toughening agent is added, so that the prepared composition has excellent impact toughness and good light transmission performance; meanwhile, a polyether amide block copolymer is also introduced, so that the corrosion of an organic solvent is resisted, the organic solvent is effectively prevented from permeating into the composition, the damage of a chemical solvent, especially medical alcohol, to the composition is reduced, and the alcohol resistance is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically to a PMMA / SAN resin composition and a preparation method and application thereof. Background Art

[0002] PMMA / SAN resin is a highly transparent resin material with a light transmittance of more than 80% in daily light. It also has good impact resistance and excellent processing properties. It is widely used in transparent parts in home appliances, consumer electronics and toy industries.

[0003] At present, the research on PMMA / SAN resin is mainly aimed at improving its transparency and mechanical properties; for example, patent CN114230953A proposes a dimensionally stable, mechanically enhanced transparent resin composition, which uses SAN and PMMA as matrix resins, MBS as a toughening agent, and SMA as a transparent modifier. When glass fiber is added, the mechanical properties and dimensional stability of the transparent resin are improved while maintaining excellent transparency.

[0004] As consumers pay more and more attention to health in recent years, 75% medical alcohol is often used to disinfect the shells of electronic products and toys that are frequently in contact with the human body. However, PMMA / SAN resin is intolerant to alcohol because the methyl methacrylate (MMA) component in it is intolerant to alcohol. When it comes into contact with alcohol under stress, it will develop microcracks of varying degrees or even break in a short period of time, resulting in the gradual restriction of the application of PMMA / SAN resin in these products that are frequently in contact with alcohol. However, there are no relevant reports on the research on improving the alcohol resistance of PMMA / SAN resin materials while ensuring that the transparency and mechanical properties of PMMA / SAN resin materials meet the requirements of use. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects and shortcomings of the existing PMMA / SAN resin composition and provide an alcohol-resistant, transparent and high-toughness PMMA / SAN resin composition which can take into account both transparency and mechanical properties and also has excellent alcohol resistance.

[0006] Another object of the present invention is to provide a method for preparing a PMMA / SAN resin composition.

[0007] Another object of the present invention is to provide a use of the PMMA / SAN resin composition in preparing transparent parts of household appliances, consumer electronics or toys.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] The present invention protects a PMMA / SAN resin composition, comprising the following components in parts by weight:

[0010]

[0011] The acrylonitrile content in the SAN resin is 18-25 wt.%.

[0012] The PMMA / SAN resin composition of the present invention adopts PMMA and SAN as matrix resins, optimizes the proportion of each component, and adds an MBS toughening agent, so that the prepared composition has excellent impact toughness and good light transmission performance; at the same time, a polyether amide block copolymer is introduced, which contains a polyether soft segment and has a certain elastomer toughening effect, and an amide hard segment has good solvent resistance and excellent fluidity, and is easily enriched on the surface in the component system, so as to resist the erosion of organic solvents, effectively prevent the organic solvent from penetrating into the composition, improve the protection effect on methyl methacrylate (MMA) components and rubber components in the material, reduce the damage of chemical solvents, especially medical alcohol, to the composition, and enhance the alcohol resistance.

[0013] In addition, the SAN resin and PMMA resin of the present invention can be derived from PCR recycled materials. By controlling the ratio of PMMA resin and SAN resin and the acrylonitrile content in the SAN resin, the PMMA / SAN blend can have a suitable refractive index. At the same time, by adding MBS toughening agent and polyetheramide block copolymer with a lower refractive index difference, the material can have excellent impact toughness and light transmittance. The use of PCR recycled materials enables low-carbon sustainable development of home appliances, consumer electronics and toy industries.

[0014] In some embodiments, the mass ratio of the PMMA resin to the SAN resin is (1.5-3):1.

[0015] In some embodiments, the PMMA resin capable of achieving the purpose of the present invention can be 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts or any value within the range of above.

[0016] In some embodiments, the SAN resin capable of achieving the purpose of the present invention may be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts or any value within the range of more than 60 parts.

[0017] In some embodiments, the content of MBS toughening agent that can achieve the purpose of the present invention can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts or any value within the range of above.

[0018] In some embodiments, the content of the polyetheramide block copolymer capable of achieving the purpose of the present invention can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts or any value within the range of above.

[0019] In some embodiments, the refractive index difference between the PMMA / SAN blend composed of the PMMA resin and the SAN resin and the MBS toughening agent and the polyether amide block copolymer is ≤0.2; more preferably, the refractive index difference is ≤0.1.

[0020] In some embodiments, the refractive index of the PMMA / SAN blend is 1.50-1.53, preferably 1.515-1.522.

[0021] Among them, the refractive index of PMMA is 1.490-1.495, and the refractive index of SAN is between 1.565-1.575. The higher the AN content, the lower the refractive index of SAN, which is beneficial to reducing the refractive index difference between PMMA resins. However, the higher the AN content, the worse the compatibility with PMMA, resulting in a larger haze of the blend. The present invention controls the refractive index of the PMMA / SAN blend and reduces the haze of the blend by controlling the ratio of PMMA and SAN and the content of AN in the SAN resin.

[0022] In some embodiments, the MBS toughening agent is methyl methacrylate-butadiene-styrene copolymer, and the refractive index is 1.50-1.52;

[0023] Preferably, the butadiene content in the MBS toughening agent is 60-70 wt.%.

[0024] In some embodiments, the refractive index of the polyetheramide block copolymer is 1.50-1.52; the refractive index is tested according to standard ISO 489:2022 method A; and the thickness of the prepared sample is 1.0 mm.

[0025] In some embodiments, the polyether segment of the polyetheramide block copolymer is selected from polyoxyethylene (PEO) and polyoxypropylene.

[0026] In some embodiments, the amide segment of the polyetheramide block copolymer is selected from at least one of PA6, PA11 or PA12.

[0027] Preferably, the polyetheramide block copolymer is PA6-b-PEO and / or PA12-b-PEO.

[0028] In some embodiments, the SAN resin has a melt flow rate of 20-40 g / 10 min at 220° C. and 10 kg; the melt flow rate is tested according to ISO 1133 standard.

[0029] In some embodiments, the PMMA resin has a melt flow rate of 2-20 g / 10 min at 230° C. and 3.8 kg.

[0030] In some embodiments, the invention further comprises: 0.1-2 parts of antioxidant and 0.1-2 parts of lubricant.

[0031] Preferably, the antioxidant is a hindered phenol antioxidant and / or a phosphite antioxidant;

[0032] Specifically, the hindered phenol antioxidant is selected from Antioxidant 1010, and the phosphite antioxidant is selected from Antioxidant 168.

[0033] Preferably, the lubricant is any one of vinyl bisstearamide, polysiloxane, calcium stearate, magnesium stearate, zinc stearate, PE wax or PP wax, or a mixture of two or more thereof.

[0034] A method for preparing a PMMA / SAN resin composition comprises the following steps: uniformly mixing various raw material components in a formula amount, and performing melt blending and extrusion to obtain the PMMA / SAN resin composition.

[0035] In some embodiments, the steps are included: after uniformly mixing the raw material components in the formula in a mixing device, melt-blending and extruding on a mechanical device, and pelletizing and drying after water cooling and / or air cooling to obtain the PMMA / SAN resin composition.

[0036] Preferably, the mixing device is a low-speed mixing device with a rotation speed of 50 rpm-300 rpm.

[0037] Preferably, the processing temperature of the mechanical device is 150° C. to 240° C., and the rotation speed is 50 rpm to 400 rpm.

[0038] Preferably, the mechanical device is a twin-screw extruder or an internal mixer.

[0039] More preferably, when the mechanical device is a twin-screw extruder, the temperature of zones 1 to 2 is 120°C to 180°C, the temperature of zones 3 to 5 is 180°C to 220°C, the temperature of zones 5 to 10 is 180°C to 220°C, and the screw speed is 200rpm to 400rpm.

[0040] The invention discloses an application of a PMMA / SAN resin composition in preparing transparent parts of household appliances, consumer electronic products or toys.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The invention provides a PMMA / SAN resin composition. The PMMA resin and the SAN resin are used as matrix resins, the proportion of each component is optimized, and an MBS toughening agent is added, so that the prepared composition has excellent impact toughness and good light transmission performance; at the same time, a polyether amide block copolymer is introduced, which contains a polyether soft segment and has a certain elastomer toughening effect, and the amide hard segment has good solvent resistance and excellent fluidity. The amide hard segment is easily enriched on the surface in the component system, so as to resist the erosion of organic solvents, effectively prevent the organic solvent from penetrating into the composition, improve the protection effect on the MMA component and the rubber component in the material, reduce the damage of chemical solvents, especially medical alcohol, to the composition, and enhance the alcohol resistance. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0044] The raw materials used in the following examples and comparative examples are as follows:

[0045] SAN resin:

[0046] SAN 1#: SAN 310N TR, Kumho Chemical Co., Korea, AN content 20%, standard ISO 1133 test at 220°C, 10kg conditions, melt flow rate is 30g / 10min.

[0047] SAN 2#: SAN KFA-130, Liaoning Jinfa Technology Co., Ltd., AN content 25%; standard ISO 1133 test at 220°C, 10kg conditions, the melt flow rate is 38g / 10min.

[0048] SAN 3#: SAN NF2200, chemical fiber company, AN content 25%, standard ISO 1133 test at 220℃, 10kg conditions, melt flow rate is 29g / 10min.

[0049] SAN 4#: SAN 350NA, Kumho Chemical Co., Ltd., South Korea, AN content 32%; standard ISO 1133 test at 220°C, 10kg conditions, melt flow rate is 33g / 10min.

[0050] rSAN: AN content 22%; standard ISO 1133 test at 220°C, 10kg conditions, the melt flow rate is 36g / 10min.

[0051] PMMA resin:

[0052] PMMA 1#: PMMACM-211, Chi Mei Company; standard ISO 1133 test at 230°C, 3.8kg, melt flow rate is 16g / 10min, refractive index is 1.492.

[0053] PMMA 2#: PMMACM-207, Chi Mei Company; standard ISO 1133 test at 230°C, 3.8kg, melt flow rate is 8.5g / 10min, refractive index is 1.493.

[0054] PMMA 3#: PMMACM-205, Chi Mei Company; standard ISO 1133 test at 230°C, 3.8kg, melt flow rate is 2.0g / 10min, refractive index is 1.491.

[0055] rPMMA: Standard ISO 1133 test at 230°C, 3.8kg, the melt flow rate is 6.5g / 10min, and the refractive index is 1.492.

[0056] MBS toughening agent (methyl methacrylate-butadiene-styrene copolymer):

[0057] Toughening agent 1#: EM500, LG Chemical of South Korea, butadiene content 65%, refractive index 1.51;

[0058] Toughener 2#: EXL2620, Rohm and Haas, USA, butadiene content 60%, refractive index 1.52.

[0059] Polyetheramide block copolymer:

[0060] Polyetheramide copolymer 1# (PA6-b-PEO): PELESTAT NC6321, Sanyo Chemical, Japan, refractive index 1.514.

[0061] Polyetheramide copolymer 2# (PA6-b-PEO): PELESTAT 6200, Sanyo Chemical, Japan, refractive index 1.510.

[0062] Polyetheramide copolymer 3# (PA12-b-PEO): E40-S3, Arkema Chemicals, France, refractive index 1.508.

[0063] Polyamide PA6: HY-2000A, Haiyang Technology, refractive index 1.530.

[0064] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, commercially available.

[0065] Lubricant: ethylene bis stearamide (EBS), commercially available.

[0066] MABS resin: MABS TR558, LG Chemical Co., Ltd., South Korea.

[0067] The refractive index of PMMA / SAN below is tested according to standard ISO 489:2022 method A, with a sample thickness of 1.0 mm.

[0068] The preparation method of the PMMA / SAN resin composition in the following examples and comparative examples comprises the following steps: uniformly mixing the raw material components of the formula in a low-speed mixing device at a rotation speed of 50 rpm-300 rpm, melt-blending and extruding in a twin-screw extruder, wherein the temperature of the first to second zones of the twin-screw extruder is 120° C.-180° C., the temperature of the third to fifth zones is 180° C.-220° C., the temperature of the fifth to tenth zones is 180° C.-220° C., the screw speed is 200 rpm-400 rpm, air-cooling and pelletizing, and drying to obtain the PMMA / SAN resin composition.

[0069] Examples 1 to 17

[0070] This embodiment provides a series of PMMA / SAN resin compositions, and the raw material components thereof are shown in Table 1.

[0071] Table 1 Raw material components of Examples 1 to 17 (parts by mass)

[0072]

[0073]

[0074] Comparative Examples 1 to 7

[0075] This comparative example provides a series of PMMA / SAN resin compositions, and the raw material components thereof are shown in Table 2.

[0076] Table 2 Raw material components of comparative examples 1 to 7 (parts by mass)

[0077]

[0078] Performance Testing

[0079] The PMMA / SAN resin compositions of Examples 1 to 17 and Comparative Examples 1 to 7 were subjected to the following experimental tests. The results are shown in Tables 3-4.

[0080] Experimental methods:

[0081] Drop hammer impact height: tested in accordance with GB / T 14153-93 standard, load 2kg, hammer head radius 5mm, sheet specification 100*100*2mm;

[0082] Light transmittance and haze: tested in accordance with GB / T 2410-2008 standard, sample thickness 2mm;

[0083] Alcohol stress cracking resistance test: prepare tensile specimens according to ASTM D638 standard, apply fixed strain to the tensile specimens, the deflection of the test fixture is 2.54cm, and then apply 75% medical alcohol every 5 minutes, and record the time when the specimen cracks.

[0084] Table 3

[0085]

[0086] Table 4

[0087]

[0088] The results show that the PMMA / SAN resin composition of the present invention has a drop hammer impact height of more than 30 mm, a light transmittance of more than 83%, a haze of less than 18%, and an alcohol stress cracking time of >30 min; it has high transparency and impact resistance, and can effectively resist alcohol erosion. When rSAN resin and rPMMA resin are used, their impact toughness, light transmittance and alcohol resistance do not change significantly, so that the present invention can realize the preparation of alcohol-resistant, transparent and high-toughness PMMA / SAN resin compositions using PCR recycled materials, and achieve low-carbon sustainable development.

[0089] Compared with Example 1, the acrylonitrile (AN) content of the SAN resin component in the PMMA / SAN resin composition of Comparative Example 1 is too high, which makes the refractive index of the PMMA / SAN blend differ greatly from that of the other components, resulting in decreased light transmittance and increased haze.

[0090] Compared with Example 1, the polyetheramide copolymer is not added in Comparative Example 2, and the alcohol stress cracking resistance time is only 4 minutes, which is easily corroded by alcohol. PA6 is used in Comparative Example 3 to replace the polyetheramide copolymer. Since the refractive index of PA6 material is too large, the light transmittance of the material decreases and the haze increases.

[0091] Compared with Example 1, when the proportion of SAN resin in the PMMA / SAN blend in Comparative Example 4 is too large, or when the proportion of SAN resin in the PMMA / SAN blend in Comparative Example 5 is too small, the light transmittance of the material decreases and the haze increases.

[0092] Compared with Example 1, no MBS toughening agent was added in Comparative Example 6, resulting in a significant decrease in impact resistance.

[0093] Comparative Example 7 is a commercially available MABS resin, which has good light transmittance and low haze, but its impact resistance is insufficient and cannot resist the erosion of alcohol.

[0094] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A PMMA / SAN resin composition, characterized in that: The composition includes the following components in parts by weight: The acrylonitrile content in the SAN resin is 18-25 wt.%.

2. The PMMA / SAN resin composition according to claim 1, characterized in that The mass ratio of the PMMA resin to the SAN resin is (1.5-3):

1.

3. The PMMA / SAN resin composition according to claim 1, characterized in that: The butadiene content in the MBS toughening agent is 60-70 wt.%.

4. The PMMA / SAN resin composition according to claim 1, characterized in that: The amide segment in the polyether amide block copolymer is at least one of PA6, PA11 or PA12.

5. The PMMA / SAN resin composition according to claim 1 or 3, characterized in that: The refractive index of the polyether amide block copolymer is 1.50-1.

52.

6. The PMMA / SAN resin composition according to claim 1, characterized in that: The refractive index difference between the PMMA / SAN blend and the MBS toughening agent and the polyether amide block copolymer is ≤0.

2.

7. The PMMA / SAN resin composition according to claim 1, characterized in that: The SAN resin has a melt flow rate of 20-40 g / 10 min at 220° C. and 10 kg.

8. The PMMA / SAN resin composition according to claim 1, characterized in that: The PMMA resin has a melt flow rate of 2-20 g / 10 min at 230° C. and 3.8 kg.

9. A method for preparing the PMMA / SAN resin composition according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing various raw material components in a formula amount, and melt-blending and extruding to obtain the PMMA / SAN resin composition.

10. Use of the PMMA / SAN resin composition according to any one of claims 1 to 8 in preparing transparent parts of household appliances, consumer electronics or toys.

Citation Information

Cited By

  • Alcohol-resistant transparent high-toughness PMMA / san resin composition, and preparation method therefor and use thereof

    WO2026149522A1